2019
DOI: 10.1126/sciadv.aax8030
|View full text |Cite
|
Sign up to set email alerts
|

Active role of elongation factor G in maintaining the mRNA reading frame during translation

Abstract: During translation, the ribosome moves along the mRNA one codon at a time with the help of elongation factor G (EF-G). Spontaneous changes in the translational reading frame are extremely rare, yet how the precise triplet-wise step is maintained is not clear. Here, we show that the ribosome is prone to spontaneous frameshifting on mRNA slippery sequences, whereas EF-G restricts frameshifting. EF-G helps to maintain the mRNA reading frame by guiding the A-site transfer RNA during translocation due to specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 40 publications
10
83
0
Order By: Relevance
“…Interestingly, all three suppressor mutants had mutations affecting the essential translation elongation factor G, in two strains (GP3101 and GP3103) the highly conserved Ala-579 was replaced by a Val (see S9 Fig ). Ala-579 is located in immediate vicinity of a loop (Loop II) that is required for tRNA translocation in the ribosome [ 76 , 77 ], suggesting that the mutation interferes with translation. In the third strain (GP3102) we found an A21T substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, all three suppressor mutants had mutations affecting the essential translation elongation factor G, in two strains (GP3101 and GP3103) the highly conserved Ala-579 was replaced by a Val (see S9 Fig ). Ala-579 is located in immediate vicinity of a loop (Loop II) that is required for tRNA translocation in the ribosome [ 76 , 77 ], suggesting that the mutation interferes with translation. In the third strain (GP3102) we found an A21T substitution.…”
Section: Resultsmentioning
confidence: 99%
“…During translocation, A and P site tRNAs move together with their respective mRNA codons. It has been shown that bacterial EFG is crucial to maintain the mRNA‐tRNA interaction during tRNA movement, as the absence or mutation of EFG leads to increased frameshifting and decreased translocation efficiency (Martemyanov et al , ; Savelsbergh et al , 2000a; Holtkamp et al , ; Peng et al , ; Zhou et al , ). An important parameter to maintain the mRNA reading frame is the interaction of mtEFG1 domain IV with the tRNA‐mRNA module via two apical loops that engage with the minor groove of the codon–anticodon base pairs and with the backbone of the peptidyl‐tRNA (Gao et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…This interaction is conserved in mitochondrial translocation as mtEFG1 retained a critical di‐glycine motif (G544/G545) at the tip of loop1 that enables the loop to sterically fit into the minor groove of the mRNA‐tRNA module (Figs C and EV3C). Loops 1 and 2 in addition contain conserved residues Q542 and H617 (Q500 and H573 in T. thermophilus ) that contact the tRNA backbone and prevent tRNA slippage (Figs C and EV3C) (Gao et al , ; Ramrath et al , ; Zhou et al , ; Peng et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…EF-G residues located in the tip of domain IV interact with the anticodon stem-loop of the A-site tRNA during translocation to the P site ( Zhou et al, 2013 ) and mutations in this domain slow the rate of translocation ( Rodnina et al, 1997 ; Savelsbergh et al, 2000 ). Recent studies using slippery codon sequences where spontaneous frameshifting occurs, EF-G can restrict frameshifting and helps to maintain the mRNA frame ( Peng et al, 2019 ). It is therefore an enticing hypothesis that EF-G may have a role in mRNA frame maintenance in addition to its established function in translocation.…”
Section: Discussionmentioning
confidence: 99%